The Role of the International Criminal Court (ICC) in Resolving Israeli War Crimes Against Palestinian Civilians - Dion Untung Wijaya; Feri Irawan; Gilang Respati (Formosa Journal of Sustainable Research, 2024)
The Israeli-Palestinian conflict, especially in the context of war crimes that harm Palestinian civilians, has become the focus of world attention. The International Criminal Court (ICC), based on the 1998 Rome Statute, has jurisdiction over crimes of genocide, crimes against humanity, war crimes and crimes of aggression. This research analyzes the role of the ICC in dealing with Israeli war crimes against Palestinian civilians. The ICC, as a permanent international tribunal, can try perpetrators of war crimes regardless of their official capacity in their country of origin. The ICC has the potential to provide justice for Palestinian victims of war crimes, although the challenge is to exercise jurisdiction over non-party states and ensure its decisions comply with international expectations for justice and peace